Total Esophageal Avulsion at the Esophagogastric Junction after Blunt Trauma. (8th April 2013) - Uygun, Ibrahim; Otcu, Selcuk; Aydogdu, Bahattin; Okur, Mehmet Hanifi; Arslan, Mehmet Serif
Abstract : Total avulsion and transection of the esophagus at the esophagogastric junction are very rare after blunt trauma, and their management is challenging. Here, we present the case of a boy with this injury. To date, only two cases have been reported in children. One was treated successfully and the other died. The initial emergency operation should aim to save the life and native esophagus. Therefore, a primary or early thoracal end esophagostomy with gastrostomy should be performed, while primary repair should not be.